Factors affecting problematic use of psychoactive substances among bachelor level students: A mixed methods study from Hill and Terai of Nepal - Basnet, Puspa; Devkota, Gaurav; Agrawal Sagtani, Reshu Agrawal Sagtani; Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2020)
Introduction: Adolescents start experimenting with licit substances which later worsen to use of more addictive illicit substances. Genetic and environmental vulnerabilities affect use of psychoactive substances with family support, competence, and psychological well-being acting as protective factors. This study aimed to identify the prevalence of problematic use of psychoactive substances among bachelor level students and factors affecting the problematic use.Method: A cross-sectional study was conducted among 50 bachelor level students selected purposively from a private college of Kathmandu metropolitan city and five in-depth and key informant interviews of bachelor level students, guardian, and teachers from Kohalpur municipality. Cronbach’s alpha was calculated for each of the tools used and prevalence of problematic use of psychoactive substances was assessed.Result: Prevalence of problematic use of psychoactive substances among lifetime users was 51.4%. The factors significantly associated with problematic use of psychoactive substances were sex and social discrediting by peers. Qualitative analysis identified many risk and protective factors at individual, interpersonal, and sociocultural level.Conclusion: High prevalence of lifetime psychoactive substance use and high percentage of problematic use of psychoactive substances among substance users requires intervention at different socio-ecological level.